Approaches to cross-cultural psychiatry - Murphy, Jane M.; Leighton, Alexander H. (Alexander Hamilton), 1908-2007 (Cornell University Press, 1965)
From specialists in several disciplines--psychiatry, general medicine, anthropology, sociology, and social work--the editors of this volume have assembled reports on a search for ways of identifying mentally ill people in other cultures and of determining what kinds of sociocultural factors influence the origin, course, and outcome of psychiatric disorders. The contributors have approached the subject through reviews of the literature, seminar discussions, and exploratory field studies carried out in Nova Scotia and among Eskimos, Navahos, and Mexicans.The book provides a methodological approach to important issues and problems in an area in which there is as yet only limited and uncertain knowledge. It will be useful to psychiatrists and epidemiologists working outside their own cultures, to psychologists and anthropologists, and as a handbook for specialists in mental health.